Risk Factors Affecting Alternate Segregation in Blastocysts From Preimplantation Genetic Testing Cycles of Autosomal Reciprocal Translocations - Xie, Pingyuan; Hu, Liang; Peng, Yangqin; Tan, Yue-qiu; Luo, Keli; Gong, Fei; Lu, Guangxiu; Lin, Ge (Frontiers in Genetics, 2022)
Reciprocal translocations are the most common structural chromosome rearrangement，and are associated with reproductive problems. To analyze factors that could influence meiotic segregation patterns in blastocysts for reciprocal translocation heterozygotes. Segregation patterns of quadrivalent in 10846 blastocysts from 2871 preimplantation genetic testing cycles of reciprocal translocation heterozygotes were analyzed.The percentage of normal/balanced blastocysts was 34.3%, and 2:2 segregation was observed in 90.0% of blastocysts. Increased TAR1 (the ratio of translocated segment 1 over the chromosome arm) as an independent protective factor associated with the increase of alternate segregation (P=0.004). Female gender and involvement of an acrocentric chromosome (Acr-ch) as independent risk factors reduced alternate segregation proportion(P<0.001). Of note, a higher TAR1 reduced the proportion of adjacent-1 segregation(P<0.001); longer translocated segment and female gender increased the risk of adjacent-2 segregation (P=0.009 and P<0.001, respectively). Female gender and involvement of an Acr-ch enhanced the ratio of 3:1 segregation (P<0.001 and P=0.012, respectively). In conclusion, autosomal reciprocal translocations carriers have reduced proportion of alternate segregation in blastocysts when involvement of an Acr-ch, female gender, and lower TAR1. These results may provide more appropriate genetic counseling for couples with autosomal reciprocal translocation on their chances of producing normal/balanced blastocysts.